A Review of Investigation on Strength Development of Concrete with Ordinary Portland Cement and Portland Composite Cement - Mohd Akhir, Mohamad Amirul Azri; DAVID YEOH ENG CHUAN (Recent Trends in Civil Engineering and Built Environment, 2023)
Nowadays, the construction of the building has been using concrete as the main ingredient for their structure. It can indicate as the core for production of each building. The concrete must be in its best condition to prevent the structure works from having any problem during the phase of construction. Concrete in general is a mixture of fine aggregate, coarse aggregate, cement, and water. For cement, there has been two type of cement that has been used now in construction which is Portland cement and composite cement. For Portland cement it is the composition of calcium compound, silica, alumina, and iron oxide that has been through chemical process. For composite cement, it is a mixture of high-quality clinker, fly ash, granulated slag, and gypsum. But lately there has been high demand for the usage of composite cement in the concrete mix. For this research it will indicate the review for strength of concrete with usage between the two types of cement which is Portland cement and fly ash composite cement. The review will be write based on the previous research that has been done. The data will be sought to find the pattern for development of compressive strength of concrete that contain Ordinary Portland Cement and Fly ash Composite Cement. The data collected also will be analysis for the increment gain for the compressive strength development between the period between day 1 to day 365.